The Demand for Gratitude as a Restraint on the Use of Child Labor: A Hypothesis - Oded Stark; Wiktor Budzinski (Institute of Labor Economics (IZA), 2022)
We study a parent's demand for gratitude from his child. We view this demand as an intervening variable between the parent's earnings and the incidence of child labor. The demand for gratitude arises from the desire of a parent to receive care and support from his child late in life, while the inclination of the child to provide this support during his adulthood is determined by how the child was treated by his parent during childhood. Specifically, we model the child's gratitude as an inverse function of the intensity of his labor in childhood. We show that when we keep the child's (imputed) wage constant, the intensity of child labor decreases with the parent's earnings. However, when we make the child's (imputed) wage a function of the parent's earnings, then the outcome can be different. With the help of a numerical example, we show that the pattern of child labor related to the parent's earnings can be U-shaped.
Keywords: D01; D13; D15; D64; J13; J22; O12; Q12; 330; gratitude formation; the parent's demand for care and support late in life; child labor